(untitled) (Journal of the College of Education for Women, 2019)
Gender mainstreaming is a goal for building a society characterized by justice and equality. Gender mainstreaming requires a clear understanding of the concept. Therefore, the research focuses on the concept of gender and how it was addressed in the literature through which the concepts related to gender were extracted which is represented by the role and social status through which the relationship of gender can be measured. In order to find out the basis for the different status and roles of both sexes in societies, the interpreted theories of gender were addressed, through which the most important factors affecting gender relations, such as biological, social and economic factors, as well as political systems, were discussed. Due to the changing factors temporally and spatially, gender relations are also changing. As a result of these changes, the concept of gender has become a prominent concept in various aspects of life and has been the focus of many writers, researchers and conferences on how to contribute to gender and what mechanisms contribute to the uncles. The research focused on the concept of social innovation and the role of community initiatives as a means of mainstreaming gender into development issues.